The organizational behavior reader (Prentice Hall, 2001)
For courses in Organizational Behavior, Individual Behavior in Organizations, and Industrial Psychology. This reader provides the best collection of classic, ground-breaking articles, as well as cutting-edge works in the field in a practical, reader-friendly format to support your experiential OB classroom.